Anaphora Processing and Applications 7th Discourse Anaphora and Anaphor Resolution Colloquium, DAARC 2009 Goa, India, November 5-6, 2009 Proceedings - Sobha, Lalitha Devi; Branco, António; Mitkov, Ruslan (Lecture Notes in Artificial Intelligence, 2009)
This book constitutes the refereed proceedings of the 7th Discourse Anaphora and Anaphor Resolution Colloquium, DAARC 2009, held in Goa, India, in November 2009. The 10 revised full papers presented were carefully reviewed and selected from 37 initial submissions. The papers are organized in topical sections on resolution methodology, computational applications, language analysis, and human processing.